Blockchain from farm to fork - a new business model for tracing local South African market food supply chains using blockchain technology - Oates, Natasha Lee (Financial Accounting, 2022)
One of the most prominent applications of blockchain technology is in supply chain traceability. This paper focuses on a developed case study involving a business model that makes use of blockchain technology to track the produce supply chain of a local South African farmer's market, the Oranjezicht City Farm Market. The research analyses existing literature surrounding food supply chain management approaches that leverage distributed ledger technologies, as well as the case study business model and collected data concerning the market. From this analysis, a financial model forecasting future cashflows is produced. The food supply chain for the local Cape Town Oranjezicht market is explored to determine if a blockchain-based traceability system is a viable option. Aspects of monetization and business plans are the focus and viable implementation strategies are assessed. The case study is presented using a Business Model Canvas and analysed using a SWOT analysis and Porter's Five Forces model to determine the strengths and weaknesses of the inherent business model. A financial model forecasting the future cashflows of said business model is constructed to determine the financial viability of the monetization strategy. The case study business model shows the ability to successfully provide value and solve the problems of each of the local farmer's market stakeholders, namely the farmers, the market and the customers. Analysis of the developed financial projections indicates that only the high road scenario produces a breakeven point at month 36 of the projections. This high road scenario is seen as a highly optimistic view for a financial model. Overall, it is determined that a subscription-based business model for a supply chain traceability application will contribute value and solve problems for the main environment stakeholders, but is not considered financially viable in this local, Cape Town context.